PENGUKURAN VARIABEL - Wisnu Wardhono (Bina Ekonomi, 2005)
After formulating the problem statement, measuring the variables in theoretical framework is an integral part of research an important aspect of research design. Object that can be physically measured by some calibrated instrument pose no measurement problems. In other hand, object also can be psychological measurement. However when we get into the realm of people's subjective feelings such like perceptions and attitudes, the measurement of these factors or variables become difficult. This is one of the aspects of organizational behavior and management research that adds to the complexity of research studies.